P.131 Outcomes of Nusinersen in adult and pediatric cohorts of spinal muscular amyotrophy after two years of usage at the CHU de Québec-Université Laval. (November 2021) - Michel, M; Chrestian, N; Demers, I; Déry, N; Dionne, A; Jobin, C; Lepage, K; Paquin, V; Rodrigue, X
Abstract : Background: Nusinersen is approved for spinal muscular amyotrophy type I, II, III and is available for adult and pediatric populations since January 2019 at the CHU de Québec-UL. Methods: Patients who received at least one dose of nusinersen between January 2019 and March 2021 were included. Required information was gathered from patients' charts. Results: Ten adults (70 injections) and 23 infants and children (202 injections) were included. No child but two adults stopped the therapy for personal reasons. Tests were performed at 0, 6, 18, 24 months when possible to assess efficacy, tolerability and quality of life perception (Table 1). Preliminary data shows stabilization or improvement for many tests. Conclusions: Nusinersen is well tolerated. Favorable effects were observed in both populations. A monitoring is still imperative for an objective assessment and for evaluation of the most relevant tests. Long term benefits remain to be demonstrated but results are encouraging.